Plant salt response: Perception, signaling, and tolerance - Xiao, Fei; Zhou, Huapeng (Frontiers in Plant Science, 2023)
Salt stress is one of the significant environmental stressors that severely affects plant growth and development. Plant responses to salt stress involve a series of biological mechanisms, including osmoregulation, redox and ionic homeostasis regulation, as well as hormone or light signaling-mediated growth adjustment, which are regulated by different functional components. Unraveling these adaptive mechanisms and identifying the critical genes involved in salt response and adaption are crucial for developing salt-tolerant cultivars. This review summarizes the current research progress in the regulatory networks for plant salt tolerance, highlighting the mechanisms of salt stress perception, signaling, and tolerance response. Finally, we also discuss the possible contribution of microbiota to plant salt tolerance.